ANALISYS OF HEAVY METAL CONCENTRATION OF Pb, Cu AND Zn IN SEAWATER AND SEDIMENT IN THE COASTAL WATERS OF SERGANG AND MAROK TUA OF LINGGA RIAU ISLAND PROVINCE - Audilla Pardova; Bintal Amin; Aras Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in June 2015 to determine heavy metal concentration of lead,copper and zinc in seawater and sediment in the coastal waters of Sergang and Marok Tuaof Singkep Island Riau Islands Province. The study used a survey method, samples weretaken from two stations and heavy metal analysis was carried out in Marine ChemistryLaboratory, Faculty of Fisheries and Marine Sciences, University of Riau by using AASPerkin Elmer 3110. Metal concentrations in the seawater and sediment were found to behighest in Marok Tua (Pb 0.076 mg/L, Cu 0.100 mg/L and Zn 0.335 mg/L) and thehighest concentrations in the sediment were also found in Marok Tua (Pb 6.074 μg/g, Cu6.684 μg/g and Zn 30.021 μg/g). Concentrations of Pb, Cu and Zn in sediment in thestudy area were still below the Dutch Quality Standard for metals in sediments as well asthe default value of the ERL and ERM. Based on The Potential Ecological Risk Indexcalculations it was considered that Sergang and Marok Tua coastal waters wereconsiderably safe and still has low impact on aquatic ecology.Key Words: Heavy Metals, Water, Sediment, Singkep